Conditions for Providing Sources of Investment Financing in Our Country - Erkinovna, Olimova Lola; Zokirovich, Saydirasulov Alisher (Miasto Przyszłości, 2023)
The article shows the issues of investment financing in our country, the system of financial support for entrepreneurship and increasing investment activity, the existing problems in obtaining bank loans and the solutions to them.